Answer:
w = -48
Explanation:
Step one:
Simplify w/8
6 - ( 0 - w/8) = 0
Step two:
Subtracting a fraction from a whole
Rewrite the whole as a fraction using 8 as the denominator:
6 = 6/1 = 6 times 8 over 8
Equation at the end of step 2:
w + 48/8 = 0
Step three:
When a fraction equals 0
its numerator, the part which is above the fraction line, must equal zero.
Get rid of the denominator.
w+48/8 x 8 = 0 x 8
8 cancels out the denominator
Your left with: w+48=0
Solve.
w+48=0
Subtract 48 from both sides of the equation
w = -48
You are left with
w = 48